Meta‐analysis of Autonomy at the DARPA Robotics Challenge Trials. Issue 2 (March 2015) - Murphy, Robin R.; Iagnemma, Karl; Overholt, Jim
<x xml:space="preserve">Abstract</x> The DARPA Robotics Challenge trials offer insights into how the robotics community approaches the design of intelligent systems and the role of supervision and simulation. A survey of the teams suggests that the design process may be hampered by the lack of a recognized canon of intelligent design principles and references and by the underrepresentation of artificial intelligence experts on the teams. The teams generally approached supervision and simulation as a fine‐grained execution approval activity rather than as task rehearsal for the entire action sequence.